Comparative Anti-Inflammatory Effect of Aceclofenac with Saccharin and Aceclofenac in Carrageenan-Induced Granuloma Pouch Model in Mice - Usman, Hendrizal; Umar, Salman; Aldi, Yufri; Rahmadevi, Rahmadevi; Zaini, Erizal (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
Aceclofenac is a non-steroidal anti-inflammatory drug (NSAID) that inhibits cyclooxygenase (COX) and suppresses prostaglandin synthesis. Its clinical utility, however, is limited by poor aqueous solubility and low bioavailability. This study evaluates the anti-inflammatory activity of a multicomponent crystal (MC) of aceclofenac with saccharin using a carrageenan-induced granuloma pouch model in mice. Male mice were divided into three groups (n = 3 per group): control, aceclofenac, and aceclofenac-saccharin multicomponent crystal, administered intraperitoneally. Inflammatory response was assessed via exudate volume and TNF-α levels. Both aceclofenac and MC significantly reduced exudate volume and TNF-α compared to the control (p < 0.05), with the MC group showing the greatest reduction. Although not statistically different from aceclofenac in TNF-α suppression, the MC demonstrated superior performance overall. The enhanced efficacy may be attributed to improved solubility and drug delivery. These outcomes support co-crystallization as a promising approach to optimize NSAID therapy.